2018
DOI: 10.3390/nu10101492
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Responses to Fortified Cow or Goat Dairy Drinks: A Randomised Controlled Trial

Abstract: Fortified milk drinks are predominantly manufactured from bovine (cow) sources. Alternative formulations include those prepared with hydrolysed bovine milk proteins or from alternate bovidae species, such as caprine (goat) milk. Currently, there is little data on protein digestive and metabolic responses following ingestion of fortified milk drinks. To examine the digestive and metabolic responses to commercially-available fortified milks, young adults (n = 15 males: 15 females), in a randomised sequence, inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
12
1
Order By: Relevance
“…Thus, any possible benefit of greater acute intake of these AAs abundant in SM may only be detectable within the gut or liver (27) and may not be apparent in peripheral circulation. Peripheral circulating AAs, in addition to influence from endogenous AA pools (52), are also impacted by gastrointestinal transit (57,58), or postprandial metabolic responses to meals (58)(59)(60). Importantly, the current study did not use the gold standard techniques of isotopically labeled foods to precisely track the fate of all ingested AAs, which limits the current interpretation of the AA appearance differences.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, any possible benefit of greater acute intake of these AAs abundant in SM may only be detectable within the gut or liver (27) and may not be apparent in peripheral circulation. Peripheral circulating AAs, in addition to influence from endogenous AA pools (52), are also impacted by gastrointestinal transit (57,58), or postprandial metabolic responses to meals (58)(59)(60). Importantly, the current study did not use the gold standard techniques of isotopically labeled foods to precisely track the fate of all ingested AAs, which limits the current interpretation of the AA appearance differences.…”
Section: Discussionmentioning
confidence: 96%
“…Higher fat ( 45 ) and energy content ( 49 ) are known to slow gastric emptying and fat specifically has been shown to increase the jejunal transit time ( 50 ). Variation in milk protein sequences [such as those between SM and CM ( 28 )] and protein integrity [hydrolyzed or whole protein ( 37 )], impact digestive products ( 28 ) and gastric emptying ( 37 ) or incretin responses ( 51 ). Other protein-related effects, such as those observed with A1 β-casein, have also been shown to impact lactose malabsorption and related symptoms ( 30 ), however the mechanisms for this are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Milan et al (141) reported that whole goat-protein fortified milk, compared to whole cow-protein fortified milk, was digested and metabolized similarly (despite the differences in their inherent nutrient composition) in young adults (aged 18-28 years). However, they dissolved paracetamol in fortified milk drinks before giving it to the participants for consumption (plasma paracetamol levels were used as a marker for gastric emptying).…”
Section: Protein Digestionmentioning
confidence: 98%